NILAI SOSIAL-RELIGIUTAS PADA AKUNTANSI PERTANIAN - Latifah, Eny; Abdullah, Rudi (JIDE : Journal Of International Development Economics, 2023)
This research aims to understand the values contained in agricultural production costs. This research uses the Islamic paradigm as its research paradigm. The Islamic paradigm views that everything that exists comes from God and will return to God. In addition, the Islamic paradigm also views that there is no contradiction between faith-worship and knowledge-pious deeds and runs in harmony. The results of this study show that the use of the Islamic paradigm in this study clearly opens our understanding of the existence of hidden values in the farming process which in fact can shape the character of farmers into a complete human being, namely a human being who is physically and mentally prosperous and has divine awareness.   In addition, this study also shows that farming activities carried out by Javanese farmers are not only limited to fulfill life but also to revive the universe and the positivist paradigm cannot fully capture the values contained in production costs because the positivist paradigm views the inner welfare of farmers reflected in various social and ritual activities for agricultural activities as production inefficiencies.